Commemorating the Crimean, South African and First World Wars: A Case-Study of the Royal Engineers, 1856–1922. (2nd April 2020) - Donaldson, Peter
Abstract : The First World War is often held to be a watershed in the memorialisation of war in Britain. Through an exploration of the Royal Engineers' commemorative space at their headquarters in Chatham, this article argues that the post–1918 war memorial boom displays not only divergences from, but also continuities with, Victorian and Edwardian practices. Thus, although the mass volunteerism and conscription of 1914–1918 resulted in both the rank and file and the bereaved being drawn into the memorialisation process for the first time, memorial forms and messages, nonetheless, retained firm links with commemorative rituals of the late nineteenth century.